Gingival carcinoma cuniculatum mimicking a reactive/inflammatory process - Silva, Rodrigo N.; Silveira, Heitor A. [UNESP]; Almeida, Luciana Y.; Colturato, Carla N. B.; Trivellato, Alexandre Elias; Sverzut, Cassio E.; León, Jorge E. (GN1 Sistemas e Publicacoes, 2019)
Carcinoma cuniculatum (CC), a rare variant of oral squamous cell carcinoma, presents well-differentiated neoplastic epithelial cells infiltrating the underlying submucosal or bone tissues, forming the so-called rabbit burrows filled with keratin. A 67-year-old female patient was referred complaining of a painless tumoral mass in the left mandibular body, with several months of evolution. Previous history indicated extraction of the teeth #37 and #38 and diagnosis of chronic suppurative osteomyelitis. A deep incisional biopsy revealed CC. Due to its microscopic features, suggesting an inflammatory or reactive process, strict clinicopathological correlation is necessary for the correct diagnosis of CC.
Carcinoma cuniculado gengival mimetizando um processo inflamatório/reativo
Keywords: Gingiva; Mandible; Mouth; Oral pathology; Squamous cell carcinoma